On the utility of e-learning in statistics - Wolfgang Karl Härdle; Sigbert Klinke; Uwe Ziegenhagen (Humboldt University of Berlin, Collaborative Research Center 649 - Economic Risk, 2007)
Students of introductory courses consider statistics as particularly difficult, as the understanding of the underlying concepts may require more time and energy than for other disciplines. For decades statisticians have tried to enhance understanding with the help of technical solutions such as animation, video or interactive tools. However it is not clear if the added value generated by these e-learning tools justifies the work invested. In this paper the experience with various e-learning solutions in terms of utility and the impact on teaching is discussed.
Keywords: I21; C19; 330; Statistische Methodenlehre; Computergestütztes Lernen; Kosten-Nutzen-Analyse